Pengaruh Economic Value Added (EVA) Dan Market Value Added (MVA) Terhadap Return Saham - Raja Jefry Erwin Yoshua S.; Rahma Nazila Muhammad (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study was to determine the effect of EVA and MVA on stock returns. The population used the Consumer Goods Industry sector companies listed on Bursa Efek Indonesia in 2018-2020. Sample selection used purposive sampling method using certain criteria. In analysing the research data used multiple linear regression analysis techniques. Based on the results it was found that partially with the t-test EVA had a significant on stock returns, while MVA had no significant on stock returns. Simultaneously with the F-test, EVA and MVA have a significant effect on stock returns.